Hub Location for Waterborne Transportation Networks in the Context of the Physical Internet (2026)
Transportation of goods is the backbone of modern global trade, and as economies become increasingly interconnected, the importance of designing efficient supply chains has never been more critical. The growing complexity of supply chains, driven by factors such as globalization, demand variability, and technological advancements, requires a meticulous approach to ensure goods move from their origin to destination in the most cost-effective and sustainable way. At the core of this challenge is the design of logistics networks, which involves making strategic decisions to define the key components of the network, ensuring it can address future challenges related to speed, reliability, flexibility, and environmental responsibility. In this thesis, we investigate network design problems for the transportation of goods, with a particular focus on waterborne transportation. Our research emphasizes river networks, which have been underexplored in existing literature and remain insufficiently developed in many countries, including Colombia. From an economic point of view, river transport is cheaper than road or rail, and it can also carry and store large volumes of goods at once.